2021
DOI: 10.1680/jbren.19.00050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stochastic representations of pedestrian actions on serviceability response

Abstract: Over the past 15 years, there have been some research outcomes in other disciplines, that could be used to produce new, more accurate, and realistic numerical models to characterise pedestrian loads and to significantly improve predictions of response for multiple pedestrian scenarios. However, the disconnection between fields has not facilitated this further research. Using this, the paper presents (1) a new sophisticated load model that includes the description of vertical and lateral loads, including pedest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As an example, Rezende et al [18] demonstrated the impact of both the inter-and intra-subject variability on the tuned mass damper (TMD) efficiency through simulations involving pedestrian densities up to 0.5 ped/m 2 . Similarly, Ramos-Moreno et al [19] highlighted the importance of considering the step frequency variability for individuals in simulations with multiplepedestrian scenario (pedestrian densities of 0.2 ped/m 2 and 0.2 ped/m 2 ). To describe the intra-subject variability, the variation in the gait parameters induced by a single pedestrian step-by-step needs to be evaluated [16,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Rezende et al [18] demonstrated the impact of both the inter-and intra-subject variability on the tuned mass damper (TMD) efficiency through simulations involving pedestrian densities up to 0.5 ped/m 2 . Similarly, Ramos-Moreno et al [19] highlighted the importance of considering the step frequency variability for individuals in simulations with multiplepedestrian scenario (pedestrian densities of 0.2 ped/m 2 and 0.2 ped/m 2 ). To describe the intra-subject variability, the variation in the gait parameters induced by a single pedestrian step-by-step needs to be evaluated [16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike inter-subject variability, intra-subject variability has often been neglected as its impact on vibration levels was traditionally considered insignificant [16]. Nevertheless, more recent studies demonstrated the great impact of the variability of individual walking force on the accuracy of the predicted vibration response [17][18][19]. As an example, Rezende et al [18] demonstrated the impact of both the inter-and intra-subject variability on the tuned mass damper (TMD) efficiency through simulations involving pedestrian densities up to 0.5 ped/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding human-induced loads, experimental campaigns using force plates (Parkhouse and Ewins, 2006), sensors (Moreu et al, 2020), shoe insoles (Wang H. et al, 2019), or computer vision approaches (Wang Y. et al, 2019), to mention a few, have been carried out to accurately characterize these actions. Thus, deterministic (Boniface et al, 2006;Heinemeyer et al, 2009) or stochastic (Casciati et al, 2017;Ramos-Moreno et al, 2020) models have been proposed over the years to predict the dynamic response of structures under the human actions. Codes and control design approaches consider that forces generated by human activities are the same on a flexible structure and on a rigid structure.…”
Section: Introductionmentioning
confidence: 99%